A systematic review of research on flipped language classrooms: theoretical foundations, learning activities, tools, research topics and findings. Issue 8 (2nd November 2022) - Zou, Di; Luo, Shuqiong; Xie, Haoran; Hwang, Gwo-Jen
Abstract: This paper presents a systematic review of the literature on flipped language classrooms from the perspectives of theoretical foundations, learning activities, tools, research topics and findings based on an analysis of 34 published articles. The results indicate that various research methods (e.g., tests, surveys, and interviews) were applied in the selected studies and different types of e-tools (e.g., video-watching tools, online learning platforms, online discussion tools, and video-making tools) were used in the flipped language classrooms. The findings also reveal that the flipped language classroom not only improved students' academic performance and cultivated their learning motivation but also developed their self-regulation, confidence, and higher-order thinking skills. Other research topics in the reviewed articles included the effects of external and learner factors on the flipped learning approach, students' readiness and technology acceptance, the flipped learning process, students' interactions, and teacher perceptions.